evels of blood urea nitrogen and its relationship with pregnancy in alpacas - Ancco G., Edith (2018)
The aim of this study was to determine the differences between three class intervals obtained from the levels of blood urea nitrogen (BUN) and the pregnancy rate in alpacas during the reproductive season. The study was conducted in a community cooperative in Cerro de Pasco, Peru at an altitude of 4318 m in February 2017. Fifty-two adult alpacas with more than two parturitions were evaluated. Blood samples were taken on the day of the single mount. BUN levels were determined using a commercial colorimetry kit and pregnancy was determined by ultrasonography 35 days post- mounting. The BUN levels varied between 15.07 and 46.88 mg/dl and the pregnancy rate was 59.6%. The pregnancy rate was associated with lower and higher levels of blood urea nitrogen.